Efrain Montesinos: mending hearts - Pacheco Romero, José (2008)
This is a biographical sketch of Efrain Montesinos-Mosqueira, Professor of San Fernando Faculty of Medicine, San Marcos National University, whose infancy in a rough but beautiful mountainous region shaped him to face one of the most delicate but efficient surgeries, the cardiovascular and thoracic surgery. He did not only stood out in this specialty in Ohio, USA, and Peru, but he offered it to the most needed Peruvians, creating a program (now service) of cardiovascular and thoracic surgery, at Dos de Mayo Hospital, Lima, Peru, where he attended free of charge adults and children, despite sacrifices, pains and frustrations. He also conducted, along with de Peruvian American Medical Society (PAMS), 70 medical missions in 14 Peruvian departments that attended patients in diverse medical and surgical specialties and brought equipments and materials that remained in the country. We pay this homage commemorating one year from his departure.